2019
DOI: 10.31334/trans.v1i2.308
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP PENGELOLAAN ANGGARAN PADA INSTANSI PEMERINTAH (Studi Pada Dinas Pengelolaan Keuangan, Pendapatan dan Aset Kabupaten Pandeglang Provinsi Banten)

Abstract: The purpose of this study to obtain empirical evidence about the influence of the Principles of Good Corporate Governance (Transparency, Independence, Accountability, Responsibility and Fairness) against the Budget Management in Government Agencies. The research approach used in quantitative research, was descriptive and associative. The independent variables in this study is Transparency (X1), Independence (X2), Accountability (X3), Accountability (X4) and Fairness (X5). The dependent variable in this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
1
1
Order By: Relevance
“…This study showed a different thing, namely transparency had a positive but not significant effect on the regional financial performance of East Tanjung Jabung Regency, therefore the hypothesis was rejected. This result was different from the result of studies from Maulamin, Cholik, & Alawiah (2018), Suartana & Yang (2019), Anggreni, Widanaputra, & Putri (2018), Dedy (2009), Riantiarno, Saleh, & Said (2011), Badruzaman & Irna (2012) who prove that transparency had a positive effect on regional financial performance.…”
Section: The Effect Of Transparency On Regional Financial Performancecontrasting
confidence: 80%
“…This study showed a different thing, namely transparency had a positive but not significant effect on the regional financial performance of East Tanjung Jabung Regency, therefore the hypothesis was rejected. This result was different from the result of studies from Maulamin, Cholik, & Alawiah (2018), Suartana & Yang (2019), Anggreni, Widanaputra, & Putri (2018), Dedy (2009), Riantiarno, Saleh, & Said (2011), Badruzaman & Irna (2012) who prove that transparency had a positive effect on regional financial performance.…”
Section: The Effect Of Transparency On Regional Financial Performancecontrasting
confidence: 80%
“…Tugas di dalam pemerintahan adalah memberikan pelayanan kepada masyarakat dan pegawai di instansi pemerintahannya oleh karena itu untuk menunjang kemudahan pengelolaan keuangannya, pemerintah dengan menggunakan (Sistem Informasi Pengelolaan Keuangan Daerah) SIPKD Untuk terwujudnya peningkatan kinerja para pegawai dalam Melakukan pekerjaanya (Maulamin, Cholik, & Alawiah, 2018).…”
Section: Pendahuluanunclassified